Gibran Khalil Gibran in Turkish Language (A Review of Translations of His Books and Researches on Him in Turkey): Literature - Aykut, A. Sait (Al-Ḍād Journal, 2023)
This research contains a short sketch of Gibran’s life, his intellectual background, and a review of the translations of his works and studies on him in Turkiye. It indicates that the first translation of Gibran into Turkish was done in 1946 by Ömer Rıza Doğrul. Almost all of Gibran’s works have been translated into Turkish. As the researcher mentions, the most famous translator of Gibran is Cahit Koytak, a well-known poet in Turkiye. The researcher argues that Gibran was perceived in Turkiye, as a Sufi – sage, and, had never been considered an “eccentric”, or “alien”. Furthermore, he argues that The New Age Movement of the ‘70s might have increased translations of Gibran in Turkiye. After reviewing remarkable academic activities, the researcher determined that most of the Gibran studies in Turkish academia focus on this unique author's philosophical and religious aspects. Keywords: Kahlil Gibran, Gibran Translations, Gibran Studies in Turkiye